Management Incentives, Signaling Effects and the Costs of Vertical Integration - Dirk Sliwka (Institute for the Study of Labor (IZA), 2003)
The costs of vertical integration are analyzed within a game-theoretic signaling model. It is shown that a company when being vertically integrated with a supplier may well decide to buy certain components from this supplier even at a lower quality than that offered by external sources. When the parent company decides to stop buying components from the integrated supplier, the value of the ownership share in the supplier is reduced: On the one hand, the supplier?s profit from the transactions with its parent is foregone. But on the other hand, other clients may decide against buying from this supplier as the latter?s reputation for providing an appropriate quality is damaged. The loss in value of the ownership share may outweigh the loss due to the lower quality. The anticipation of this effect leads to reduced ex ante incentives for the supplier?s management to raise quality. A spin-off may therefore be beneficial as it strengthens incentives. Costs and benefits of vertical integration are analyzed and consequences for vertically integrated companies organized in profit centers are discussed.
Keywords: M55; L22; C22; 330; vertical integration; incentives; outsourcing; signaling; Vertikale Konzentration; Lieferanten-Kunden-Beziehung; Outsourcing; Ökonomischer Anreiz; Produktqualität; Signalling; Prestige; Unternehmenswert; Kosten-Nutzen-Analyse; Profit Center; Theorie